INDIGENOUS ANCESTORS AND HEALING LANDSCAPES cultural memory and intercultural communication ... in the dominican republic and cuba - PESOUTOVA, DR. JANA. ([Place of publication not identified] SIDESTONE Press, 2019)
Crossroads of Cultural landscapes: the indigenous base of demographic changesBrief account of indigenous ancestors in colonial Hispaniola; African ancestors in Dominican demographic history; The interactions among the colonized strata; The subsequent historical development of Dominican society; A brief overview of demographic background of selected Dominican sites; Major tendencies in Cuban ethnogenesis; Colonial history of Indigenous Cuban ancestors; The heterogeneity of the Cuban ancestors of African origin; A brief overview of demographic background of selected Cuban sites
Indigenous past as the beginning of the Dominican nationIndigenous ancestors during the formation of the Cuban nation; The indigenous past in Dominican and Cuban History textbooks; The Alienation from Natural Man in the collective memory; Empty Pages in the Biography of Healing Landscapes; Indigenous ancestors transforming Caribbean Landscapes; West African ancestors shaping Caribbean landscapes; European ancestors reshaping Caribbean landscapes; The multidirectional circulation of the medicinal knowledge in the Greater Antilles; Concluding remarks
Intro; Rhizomes of Healing Landscapes; Colonial discourse and the question of cultural continuity; Forgetting Indigenous Peoples of the Greater Antilles; Approaching Healing Landscapes; Data collection and fieldwork methodology; Ethics; Outline of the dissertation; THEORETICAL AND HISTORICAL DIMENSIONS OF CARIBBEAN LANDSCAPES; Healing Landscapes from a theoretical perspective; Introduction to landscape studies; Memory landscapes; Healing Landscapes; Natural Man in the Caribbean Paradise: the origins of colonial discourse; The noble savage idea in Lesser Antilles
Mana LandscapeCave of La Mancha: Healing with Indigenous Lwas; The Cave of Saint Francis as a Healing and Memory Place of Bánica; Healing among Spiritists, Managuaco cavern, Holguín, Cuba; Cueva De los Santos Gibara, Cuba; Cuban and Dominican caverns as memory places of indigenous past; Concluding remarks; Synthesis and Conclusions. At the Crossroads of Healing Landscapes; Remembrance and Oblivion; Historical formation of Cuban and Dominican Medicinal Cultures; Constituents of healing landscapes; Memory of indigenous ancestors; Water sources and caves as ancestral places
Revising the indigenous component in demographic historiesCONTEMPORARY TRADITIONS; Qualities of the landscape in daily life; Flora as a source of alimentation; Concluding remarks; Healing in sacred and animated landscapes; Other spiritual beings in Cuban and Dominican landscapes; Illness and cure; Healing specialists; Healing Plants; Ancestral roots and rhizomes; Concluding remarks; The subaquatic realm of ancestors and other beings; Dominican Ancestral Subaquatic Dwellings; Caribbean waterbodies as reservoirs of indigenous past; Concluding remarks; Re-membering Ancestors in Caves
This book presents new interpretations of current healing practices in Cuba and the Dominican Republic juxtaposed against the European colonization of the Caribbean after 1492. By combining data from critical historical analyses and ethnographic fieldwork, this research examines current healing landscapes and their historical background in both countries.0This dissertation situates the continuous importance of non-institutional healing practices within the rich symbolism of Cuban and Dominican landscapes. More specifically, the study focuses on practices promoting physical, mental and spiritual healing of individuals and communities. It provides various examples that illustrate human interactions with divine and ancestral beings residing in places such as water sources, caverns, or manifested in plants and other natural phenomena. Data presented in this work guides our understanding of how local cultural memory plays a key role in our construction of medicinal histories, and the profound demographic and landscape transformations which shaped the healing landscapes after European conquest. Healing landscapes are also testimonies of the Cuban and Dominican ancestors' creativity, resilience, capacity to heal and find unity in the dehumanizing and alienating atmosphere of colonial violence and exploitation. This book is not aimed solely for academic public, but also those interested in Caribbean cultures, and the history of medicinal practices
Keywords: Traditional medicine -- Cuba; Traditional medicine -- Dominican Republic; Traditional medicine; Cuba; Dominican Republic